Nitric oxide and endothelin relationship in intestinal ischemia/reperfusion injury (II) - DAĞLI, EMRULLAH TOLGA; HAKLAR, GONCAGÜL; YÜKSEL, MERAL (CHURCHILL LIVINGSTONE, 2001)
Endothelins (ETs) are potent vasoconstrictors derived from vascular endothelium. They have primary roles in many pathophysiologic states including ischemia/reperfusion (I/R) injury. The relationships between nitric oxide (NO) and ETs are still under investigation. In this study on rats we want to focus on the interaction of NO and ET especially in I/R injury. For this purpose ET-1 and PD-156252, a nonselective ET receptor blocker, were given in a mesenteric I/R model and reactive oxygen species were detected directly using chemiluminescence of the ileal tissue. ET administrations to sham and I/R groups caused significant increases in NO concentrations whereas, in terms of peroxynitrite, which is a highly reactive group of free radicals, its increasing effects were seen only in I/R groups. This suggests that in I/R where superoxide levels increase together with NO, the conversion to peroxynitrite is likely and this effect is augmented with ET administration. On the other hand PD administration decreases superoxide and thereby peroxynitrite levels and this study shows that the effect of PD-156252 is established through this mode of action. These data suggest therapeutic approaches that may be beneficial in the treatment of I/R injury. (C) 2001 Harcourt Publishers Ltd.
Keywords: MESENTERIC ISCHEMIA-REPERFUSION; OXYGEN RADICALS